(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The study focused on developing and statistically optimizing sitagliptin-loaded fast-dissolving tablets (FDTs) utilizing a systematic DoE-based approach to enhance oral drug delivery and patient compliance in type 2-diabetes management. FDTs were prepared via direct compression with varying concentrations of variable excipients, Crospovidone (superdisintegrant) and Avicel 102 (binder) as part of a 3² full factorial design. The study assessed their impact on formulation attributes specifically hardness and disintegration time, alongside pre- and post-compression characteristics, dissolution performance, and stability over time. All developed formulations met pharmacopoeial standards. The optimized batch (B7) disintegrated in 34±3 seconds with adequate hardness of 4.5±0.09 kg/cm² and achieved 99.11% drug release within 30 minutes. Statistical analysis confirmed significant effects of both excipients, with crospovidone having a greater influence on disintegration. Stability studies over three months indicated no significant changes in key parameters. The results demonstrated a robust, cost-effective sitagliptin FDTs with improved dissolution properties, particularly beneficial for those with dysphagia or requiring immediate pharmacological response.